Pengembangan Sistem Pakar Menggunakan Metode Papi Kostick Untuk Tes Kepribadian - Sugiyatno Sugiyatno; Parasian D.P Silitonga; Uning Lestari (STMIK IKMI Cirebon, 2021)
This paper is a report on the results of developing an expert system using the Papi Kostick method which is used to test the personality of employees in a company. Papi Kostick method to evaluate individual behavior and work style in relation to work situations. The researcher's system development process uses the Software Development Life Cycle (SDLC) method. This expert system is implemented web-based. The tests used are validation testing and expert system accuracy testing. The test results are 100% which shows that the functionality of the system can run well according to the list of requirements. The results of the accuracy test show that the expert system using the Papi Kostick method can function properly. The results of the assessment, the company can see the progress and ability of its employees in doing certain jobs well and the suitability of employees with the workplace through personality tests. Assessment of employee behavior and work style is also useful for companies in providing feedback to employees and can be used as a basis for companies to conduct training, transfer, rotation and promotion of employees.